Resonance frequency analysis of laser optical fiber based on microcantilever - Mohanad Aljanabi (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The normal frequency of smart beams was originated utilizing FEM [Ansys and Comsol] code for first five modes by varying the position of actuator from the fixed end of the structure, and it has a suitable arrangement with analytically found the standard frequency. This paper includes learning a resonance frequency analysis of laser optical fiber based on microcantilever of designing magnetic actuator using Ansys and Comsol simulation. The design of optical fiber includes Nickel cantilever, two magnets and one coil that apply to force on the cantilever. After the current flows in the coil domain, the shape of microcantilever will be deformed. It will move to z- direction that depends on the force direction. Two methods including, Comsol Multiphysics, Ansys and analytical equations have been utilized to calculate the resonance frequency, current and force values. The simulation results include calculating the current (magnetic current density) and effects of the magnetic field of the coil on the cantilever (force calculation). Utilizing this method is to limit faults(errors) of optical fiber laser between transmitter and receiver system (detection system) for any time of cutting coil when the signal of a laser passes through the coil. In conculsions, resonant frequency (f_n) tuning using cantilivier presented in the resrach have larger variable range by using simulations. However,the adjusting of the system and changing the deminsions.Resolutions to this problematic contain tuning the modes of resonant frequency to produce by cantilivier with  2-magnets and coil when the signal  pass from  laser source. Based on these simulations and characterization results, the proposed assembly can be a good applicant for evolving a low price, high material platform for many biological, laser optical fiber, communication, machine learning, biosensors and biomedical applications.